Suicidality Scale: Psychometric Evidences in Peruvian Adolescents - Baños-Chaparro, J. (2022)
Quantitative, descriptive and cross-sectional study, whose objective was to analysethe sources of evidence of validity of the Suicidality Scale (SS) in Peruvian adolescents. 319 adolescents residing in the province of Ica -Peru participated, who answered the SS virtually. Structural Equation Modelling(SEM) and Item Response Theory (IRT) were applied in the statistical analysis. Results: 21% indicated that they had suicidal thoughts during the first wave of Covid-19. Likewise, the SS evidence a one-dimensional structure (CFI = .99, RMSEA = .05 [90% CI: .00-.13], SRMR = .02), acceptable reliability (ω= .87 and H = .96), suitable parameter values (αand β) and latent trait information (Ɵ), being useful in people with high levels of suicidality. Therefore, the SS proves to be a reliable, accessible and practical instrument to evaluate suicidality in Peruvian adolescents.